PENGGUNAAN MODEL PROBLEM BASED LEARNING DENGAN METODE GASING DALAM MENINGKATKAN PEMECAHAN MASALAH MATEMATIKA DI KELAS IV - Restianti, Rina; Iis Nurasiah; Arsyi Rizqia Amalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this study is the low problem solving ability of fourth grade students of SDIT Adzkia 2. The purpose of this study was to improve the problem solving ability of fourth grade students of SDIT Adzkia 2 through the use of problem-based learning model with gasing method. The subjects of this study were fourth grade students of SDIT Adzkia 2, totaling 24 students. The research method used was Kemmis and Mc Taggart class action research. Data were collected through tests and observations and then analyzed using descriptive statistical techniques. The results showed that in the pre-cycle cycle the average value obtained was 62.81 and included in the sufficient criteria. In cycle I there was an increase in problem solving ability with the average value obtained was 70.35 good criteria. There was another increase in students' problem solving skills in cycle II with an average value of 80.14 and included in the excellent criteria. It can be concluded that the use of problem-based learning models with the gasing method can improve the mathematical problem solving skills of grade IV students.